Career choice of the University of the Philippines freshmen and their correlates - Torres, Lilia Arbues 1936-
This study sought to identify and establish the correlates of the factors which influence an individual's career choice. It made use of the descriptive survey for data collection as well as various correlation procedures for statistical analyses. The sample consisted of 600 subjects, 30 percent of the 1,927 male and female freshman students in the College of Arts and Letters of the University of the Philippines Diliman Campus during the first semester of the school year 1976-1977. The instruments used included the 27-item Basic Questionnaire and the Strong Vocational Interest Blank (SVIB) Form T-399, 1966 Revision. The findings revealed that Engineering is the most attractive career program. Career choices of students is a result of the interplay of such factors as student's interests, abilities, SES, parental approval, influence of friends and other relatives, printed materials and other media, and guidance counselors. Students came to UP because of certain factors such as quality of education, low tuition fees, prestige and courses offered.